Comparison between simultaneous bilateral total hip arthroplasty with and without drainage: A retrospective cohort study. Issue 43 (28th October 2022) - Kim, Min-Gwang; Im, Chae-Jin; Jung, Woo-Chul; Yoon, Taek-Rim; Park, Kyung-Soon
Abstract : Simultaneous bilateral total hip arthroplasty (SBTHA) is an effective procedure for patients with disease bilaterally. But there is concern about increased blood loss and complications of SBTHA than staged total hip arthroplasty (THA). This study aimed to evaluate the differences in the clinical outcomes and complication rate of SBTHA with drainage and without drainage for reducing the concerns. Between October 2015 and April 2019, a retrospective cohort study was conducted with modified minimally invasive 2-incision method and a consecutive series of 41 SBTHA performed with drainage (Group I) were compared to 37 SBTHA performed without drainage (Group II). It was assessed clinically and radiographically for a mean of 2.1 ± 0.8 years (range, 1.0-4.8 years). Postoperative hematologic values (Hgb loss, total blood loss, transfusion rate), pain susceptibility, functional outcome (Harris Hip Score, Western Ontario and McMaster Universities Osteoarthritis Index score) and complication were compared in the drained group and the non-drained group. Postoperative Hgb loss (I: 2163.2 ± 698.7 g, II: 1730.4 ± 572.5 g; P = .002), total blood loss (I: 1528.8 ± 421.7 mL, II: 1237.6 ± 325.9 mL; P = .001) and mean transfusion unit (I: 0.7 ± 1.0 IU, II: 0.1 ± 0.3 IU; P < .001) were significantly lower in the without drainage group than in the with drainage group. But the morphine equivalent (I: 132.7 ± 314.1 mg, II: 732.2 ± 591.5 mg; P < .001) was significantly larger in the without drainage group. No significant difference was found between the drainage group and without drainage group in Harris Hip Score and Western Ontario and McMaster Universities Osteoarthritis Index score at final follow-up. SBTHA without drainage can reduce postoperative blood loss and the requirement for transfusion without increasing other complication. But SBTHA without drainage is more painful method than SBTHA with drainage. Therefore, SBTHA without drainage will be a good option to reduce the burden on the patient by reducing postoperative bleeding if it can control pain well after surgery. III, Retrospective case-control study.